Medical Emergencies in Dental Clinics - Hussien, Saba Zuhair; Abdul-Husein, Aola Zuhair (Majallat Jāmiʻat Bābil, 2025)
Medical emergencies in dental clinics can occur unexpectedly and encompass a range of conditions, from respiratory and cardiovascular issues to allergic reactions and neurological disorders. Dentists must be well prepared through training and continuous education to handle these emergencies promptly. Most emergencies were prevented via ideal examination of the patient and analysis of past medical history. With careful planning of emergency protocol with team approach and specialized theoretical and practical training, and many emergency conditions can be prevented; can help mitigate risks, ensuring a swift and efficient response to safeguard patient health. Medical emergencies can be happening unsuspectedly during dental treatment so patient’s life may depend on the readiness, good staff-skill training and accessibility of suitable emergency medication and tools all of which are vital for the emergency management. Most emergencies are prevented via ideal examination of the patient and analysis of past medical history.